2020
DOI: 10.1521/pedi_2018_32_382
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity in Borderline Personality Disorder: Theoretical Considerations Based on a Meta-Analytic Review of Laboratory Studies

Abstract: Emotional hyperreactivity (Linehan, 1993) is the most investigated construct in borderline personality disorder (BPD). However, experimental studies revealed mixed results on the topic. Our main objective is to comprehensively summarize the results on emotional reactivity in BPD compared to healthy controls (HCs), using a meta-analytic approach, considering different emotional response systems (physiology, behavior, selfreport). We included 31 experimental studies (1,675 subjects). We observed null to small ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 126 publications
0
10
0
4
Order By: Relevance
“…Prior work suggests no abnormalities in resting baseline skin conductance levels in BPD. (Bortolla, Cavicchioli, Fossati, & Maffei, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work suggests no abnormalities in resting baseline skin conductance levels in BPD. (Bortolla, Cavicchioli, Fossati, & Maffei, ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental settings offer higher control and better temporal resolution, but suffer from limited ecological validity, as stressors are presented outside of their natural context (assumption 2). A recent meta-analytic review found that the literature is surprisingly inconclusive concerning experimentally induced emotional reactions in BPD (Bortolla et al, 2020). While they did find moderate experimental group effects on affective self-ratings in their meta-analysis, many studies did not include a pre-measurement, potentially confounding tonic negative emotions and emotional reactivity, or only had pre- and post-task ratings, which might capture other processes than stimulus-contingent real-time responses.…”
Section: Discussionmentioning
confidence: 99%
“…While assigning patients to the two therapy groups, PSA and PDT, despite the known heterogeneity of BPD patients[ 52 ], we attempted to match patients who were comparable to one another, as far as their personality structure was concerned; however, differences in the patients' personality traits were found in both therapy groups. The fact that the assigning of patients to therapy groups depended on the availability of a therapist may be seen as a legitimate point of criticism.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have descriptive value and contributed to the foundation of clinical-relevant hypotheses that might be further investigated in an experimental study design. Emotional reactivity in patients with borderline personality disorder (BPD) due to dysfunctional processes is still a concept being developed[ 52 , 57 ]. We agree that a larger sample size would have been favorable.…”
Section: Discussionmentioning
confidence: 99%